2019
DOI: 10.1055/s-0037-1611752
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric [3+2] Cycloaddition of Olefins with Morita–Baylis–Hillman Carbonates Catalyzed by BINOL-Based Bifunctional Phosphine

Abstract: We have developed a series of novel BINOL-based phosphines. These bifunctional organocatalysts can be used in the [3+2] cycloaddition of electron-deficient olefins and Morita–Baylis–Hillman (MBH) carbonates. Moderate to excellent yields (up to >99%) and good to excellent enantioselectivities (up to 95% ee) can be obtained in the cycloaddition reaction of maleimides and MBH carbonates. The application of these novel phosphines can be further extended to the asymmetric synthesis of chiral spirooxindoles (up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In particular, Lu et al reported the first [3 + 2]-annulation of MBH carbonates with the aid of phosphane . Subsequently, organocatalytic asymmetric [3 + 2]-annulation of MBH carbonates garnered particular attention. Independently, Chen’s group has gracefully developed new MBH carbonates from isatins, which were successfully involved in organocatalytic stereoselective [3 + 2]-annulations. Notably, the organocatalytic stereoselective annulation of MBH carbonates has offered a key platform for the construction of functionalized enantioenriched carbo- and heterocycles . Although great progress has been achieved in this field, the core framework of MBH carbonates is monotonous and limited to the classical MBH adducts from aldehyde (Scheme A) and isatins (Scheme B).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Lu et al reported the first [3 + 2]-annulation of MBH carbonates with the aid of phosphane . Subsequently, organocatalytic asymmetric [3 + 2]-annulation of MBH carbonates garnered particular attention. Independently, Chen’s group has gracefully developed new MBH carbonates from isatins, which were successfully involved in organocatalytic stereoselective [3 + 2]-annulations. Notably, the organocatalytic stereoselective annulation of MBH carbonates has offered a key platform for the construction of functionalized enantioenriched carbo- and heterocycles . Although great progress has been achieved in this field, the core framework of MBH carbonates is monotonous and limited to the classical MBH adducts from aldehyde (Scheme A) and isatins (Scheme B).…”
Section: Introductionmentioning
confidence: 99%
“…Cui and coworkers have developed a series of novel BINOL‐based phosphines, and applied the catalyst 177 to catalyze the [3+2] cycloaddition reactions of electron‐deficient olefins and MBH carbonates. [ 61 ] Moderate to excellent yields (up to >99%) and good to excellent enantioselectivities (up to 95% ee) can be obtained in the cycloaddition reaction of maleimides and MBH carbonates (Scheme 42). The application of these novel phosphines can be further extended to the asymmetric synthesis of chiral spirooxindoles (up to 85% ee) (Scheme 42).…”
Section: Cycloaddition Reactions Catalyzed By Chiral Phosphinesmentioning
confidence: 99%
“…[211] In the preparation of spirocyclic compounds from 3-alkylidenenindolones, phosphines are also used as organocatalysts. [212,213] The cycloaddition of symmetric aryl ketones 164 to derivatives of 3-alkylidenenindolone 165 is catalyzed by tributylphosphine PBu 3 and leads to spirocyclic compounds 166. The diastereoselectivity of spirocyclization is moderate and does not exceed 9 : 1.…”
Section: Syntheses Of Spiro-fused Heterocycles From 3-alkylidene Indomentioning
confidence: 99%
“…[213] In the synthesis of indolones spiro-fused with cycloalkanes in the [ good enantioselectivity (74 -85 %) in the presence of the catalyst 170 (Scheme 45). [212] The intermolecular Rauhut-Currier cross-reaction of benzylidene cyclopentenone 171 or 2-cyclopentenone (or 2-cyclohexenone) 172 with 3-(dicyano)methylidene-2-oxindoles 30 or 173 is carried out with the aid of a double catalytic system that combines 2- (Scheme 46,a). A sharp decrease in the yield (up to 42 %) of the spiro-fused heterocycle 178 is observed in the reaction of cyclohexenone 172 (n = 2) with indolone 173 (R=H, R 1 = Me) when using β-nitrostyrene as an activated olefin (R 2 = Ph).…”
Section: Syntheses Of Spiro-fused Heterocycles From 3-alkylidene Indomentioning
confidence: 99%
See 1 more Smart Citation